Quantitative genetic analysis and rice kernel elongation improvement in MR219 × Mahsuri Mutan and MR219 × Basmati 370 populations - Ab Halim, Anna Arina (2019)
In Malaysia, there is increasing demand for specialty rice especially in preparing dishes such as Nasi Arab and Biryani. High kernel elongation (HKE) is one of the high-quality characteristics in rice. However, limited studies in Malaysia were done on quantitative genetics analysis of high kernel elongation that contribute to this important trait. Rice varieties such as Mahsuri Mutan and Basmati are categorized as specialty rice with kernel elongation ratio exceeding 1.6 and 2.0, respectively. The main objective of this study was to determine the genetic control and inheritance patterns of high kernel elongation of and related physico-chemical characteristics in several generations of Mahsuri Mutan and Basmati 370 crossed with MR219, also to study the ageing effect on structure of milled and cooked rice of traditional variety Mahsuri and modified variety, Mahsuri Mutan. Generation means analysis and scaling tests were carried out to estimate additive- dominance genes model. From this study, Mahsuri Mutan and Basmati 370 showed superior high kernel elongation as compared to their respective progenies. The F1 generation for both populations had intermediate HKE which were 1.65 and 1.66 for Mahsuri Mutan and Basmati 370 based populations. This study also found that ageing treatment directly affected the increasing HKE for both populations. In both populations, most of the characters including HKE were controlled by additive and dominant gene actions suggesting that selection for HKE could be done from one generation to another using recurrent selection method. Presence of epistasis for both populations where MR219 × Mahsuri Mutan showed complimentary epistasis and MR219 × Basmati 370 showed duplicate epistasis. This also shows that the HKE trait was controlled by nonallelic interaction. Estimated heritability values of HKE for both populations were moderate (54% for Mahsuri Mutan and 63% for Basmati 370). The inheritance patterns of F2 generations showed goodness of fit with the Mendelian ratio of 3:1 (normal kernel elongation ratio: high kernel elongation ratio). Phenotypic path coefficient analysis showed that CGL, PC, and LW traits had direct and indirect contribution to HKE trait. Phenotypic correlation coefficient indicated that there was a high positive correlation between HKE and water uptake ratio. The ageing treatment also showed significant difference for all the physico-chemical traits for all parental lines. Observation under SEM for milled and cooked of samples Mahsuri and Mahsuri Mutan showed that the ageing samples had more cracks on the tissue structure compared to normal rice samples. Moreover, the shape of the tissue structure also give effect on kernel elongation, for example, the hexagon structure in Mahsuri Mutan gave more elongation effect on kernel. The findings from this study on HKE of Mahsuri Mutan and Basmati 370 could be useful to breeders in selection and development of new specialty rice variety.